2022
DOI: 10.3390/ijms24010399
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Fibrillation in a Viral Amyloidogenic Domain from Combined Biochemical and Biophysical Studies

Abstract: The Nipah and Hendra viruses (NiV and HeV) are biosafety level 4 human pathogens classified within the Henipavirus genus of the Paramyxoviridae family. In both NiV and HeV, the gene encoding the Phosphoprotein (P protein), an essential polymerase cofactor, also encodes the V and W proteins. These three proteins, which share an intrinsically disordered N-terminal domain (NTD) and have unique C-terminal domains (CTD), are all known to counteract the host innate immune response, with V and W acting by either coun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The SARS-CoV-2 nucleocapsid protein (N protein) accelerates αS fibrillation through electrostatic interactions, inducing cell death [192]. It has been shown that SARS-CoV-2 proteins can also form aggregates in isolation [193,194], and similar results have been obtained for other virus species, such as the Hendra and Nipah viruses [195]. Based on the observation that human amyloids can interact with viruses, interfering with their replication, protein aggregation has been proposed as a strategy to discover new antiviral agents [196].…”
Section: Discussionmentioning
confidence: 67%
“…The SARS-CoV-2 nucleocapsid protein (N protein) accelerates αS fibrillation through electrostatic interactions, inducing cell death [192]. It has been shown that SARS-CoV-2 proteins can also form aggregates in isolation [193,194], and similar results have been obtained for other virus species, such as the Hendra and Nipah viruses [195]. Based on the observation that human amyloids can interact with viruses, interfering with their replication, protein aggregation has been proposed as a strategy to discover new antiviral agents [196].…”
Section: Discussionmentioning
confidence: 67%
“…The maturation and nucleation of the condensates formed via liquid–liquid phase separation can give rise to fibrils with amyloidogenic properties [ 103 , 104 ]. Despite the extensive literature regarding phase separation [ 100 ], the study of virus-derived amyloid-like fibrils and their role in pathogenesis is still in its infancy [ 102 , 105 , 106 , 107 ]. Attention to this field has notably increased in the last couple of years with the demonstration of amyloidogenesis by the Spike, nucleoprotein and envelope proteins of SARS-CoV-2 and their possible involvement in pathogenesis [ 108 , 109 , 110 , 111 ].…”
Section: First Steps: Contact Infection and Amplification In The Hostmentioning
confidence: 99%
“…Juliet F. Nilsson, Hakima Baroudi, Frank Gondelaud, Giulia Pesce, Christophe Bignon, Denis Ptchelkine, Joseph Chamieh, Hervé Cottet, Andrey V. Kajava, and Sonia Longhi also studied the formation of amyloid fibrils, but analyzed the aggregation behavior of an interesting viral protein, the phosphoprotein (P protein) from the Nipah and Hendra viruses (NiV and HeV), which is an essential polymerase cofactor [21]. A peculiar feature of this system is that the gene encoding the P protein in both NiV and HeV also encodes the V and W proteins.…”
mentioning
confidence: 99%
“…This analysis revealed that the ability to form fibrils is dramatically reduced by the removal of a single tyrosine independently of its position. Furthermore, the authors showed that PNT3 fibrillation can be regulated by the C-terminal half of this protein, showing an inhibitory effect on fibril formation [21]. In their research article, Mohtadin Hashemi, Siddhartha Banerjee, and Yuri L. Lyubchenko investigated the effects of membrane and free cholesterol on the early stages of the aggregation process of amyloid β (Aβ) [20].…”
mentioning
confidence: 99%
See 1 more Smart Citation